IL-2/α-IL-2 Complex Treatment Cannot Be Substituted for the Adoptive Transfer of Regulatory T cells to Promote Bone Marrow Engraftment. - Benedikt Mahr; Lukas Unger; Karin Hock; Nina Pilat; Ulrike Baranyi; Christoph Schwarz; Svenja Maschke; Andreas Michael Farkas; Thomas Wekerle (PLoS ONE)
Cell therapy with recipient Tregs achieves engraftment of allogeneic bone marrow (BM) without the need for cytoreductive conditioning (i.e., without irradiation or cytotoxic drugs). Thereby mixed chimerism and transplantation tolerance are established in recipients conditioned solely with costimulation blockade and rapamycin. However, clinical translation would be substantially facilitated if Treg-stimulating pharmaceutical agents could be used instead of individualized cell therapy. Recently, it was shown that interleukin-2 (IL-2) complexed with a monoclonal antibody (mAb) (clone JES6-1A12) against IL-2 (IL-2 complexes) potently expands and activates Tregs in vivo. Therefore, we investigated whether IL-2 complexes can replace Treg therapy in a costimulation blockade-based and irradiation-free BM transplantation (BMT) model. Unexpectedly, the administration of IL-2 complexes at the time of BMT (instead of Tregs) failed to induce BM engraftment in non-irradiated recipients (0/6 with IL-2 complexes vs. 3/4 with Tregs, p<0.05). Adding IL-2 complexes to an otherwise effective regimen involving recipient irradiation (1Gy) but no Treg transfer indeed actively triggered donor BM rejection at higher doses (0/8 with IL-2 complexes vs. 9/11 without, p<0.01) and had no detectable effect at two lower doses (3/5 vs. 9/11, p>0.05). CD8 T cells and NK cells of IL-2 complex-treated naïve mice showed an enhanced proliferative response towards donor antigens in vitro despite the marked expansion of Tregs. However, IL-2 complexes also expanded conventional CD4 T cells, CD8 T cells, NK cells, NKT cells and notably even B cells, albeit to a lesser extent. Notably, IL-2 complex expanded Tregs featured less potent suppressive functions than in vitro activated Tregs in terms of T cell suppression in vitro and BM engraftment in vivo. In conclusion, these data suggest that IL-2 complexes are less effective than recipient Tregs in promoting BM engraftment and in contrast actually trigger BM rejection, as their effect is not sufficiently restricted to Tregs but rather extends to several other lymphocyte populations.